A pH and ROS dual-responsive biomimetic EGCG nanomaterial, its preparation method and application
Patent Information
- Application Number
- CN202611383516.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-20
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedicine, and in particular to a pH and ROS dual-responsive biomimetic EGCG nanomaterial, its preparation method, and its application. Background Technology
[0002] Sepsis is a dysregulated host response disease caused by infection, often accompanied by persistent bacterial load, uncontrolled inflammatory response, increased oxidative stress, and damage to multiple organs and tissues, including the lungs, liver, and kidneys. Current treatments mainly rely on antibiotics and supportive care, but single antibacterial, anti-inflammatory, or antioxidant interventions are usually insufficient to simultaneously address the multiple pathological processes of sepsis, including infection, inflammation, oxidative stress, and multi-organ damage.
[0003] Epigallocatechin gallate (EGCG) has antioxidant, anti-inflammatory and certain antibacterial activities. However, in the complex pathological microenvironment of sepsis, free EGCG and EGCG loaded using existing drug delivery methods still have problems such as limited stability, easy degradation and insufficient effective delivery in vivo. Summary of the Invention
[0004] In view of the shortcomings of the above-mentioned related technologies, the present invention provides a pH and ROS dual-responsive biomimetic EGCG nanomaterial, its preparation method and application.
[0005] Firstly, the present invention provides a pH and ROS dual-responsive biomimetic EGCG nanomaterial using the following technical solution: A pH and ROS dual-responsive biomimetic EGCG nanomaterial comprises, from the inside out, a copper-doped metal-organic framework nanocore loaded with EGCG in situ, a phenylboronic acid-functionalized hyaluronic acid layer, and an M2 macrophage membrane biomimetic layer.
[0006] Preferably, the in-situ loaded EGCG copper-doped metal-organic framework nanonucleus comprises a copper-doped ZIF-8 nanonucleus formed by coordination of zinc ions, copper ions and 2-methylimidazole and EGCG, wherein EGCG is in-situ loaded into the copper-doped ZIF-8 nanonucleus during the formation of the copper-doped ZIF-8 nanonucleus.
[0007] Preferably, the preparation of the in-situ loaded EGCG copper-doped metal-organic framework nanonucleus includes the following steps: adding a ligand solution containing 2-methylimidazole and EGCG to a metal salt solution containing zinc ions and copper ions, stirring continuously, and reacting in the dark.
[0008] Preferably, the mass ratio of 2-methylimidazole to EGCG in the ligand solution containing 2-methylimidazole and EGCG is 10-15:1.
[0009] Preferably, the molar ratio of zinc ions to copper ions in the metal salt solution containing zinc ions and copper ions is 4-6:1.
[0010] Preferably, the phenylboronic acid-functionalized hyaluronic acid layer is formed by coating an in-situ loaded EGCG copper-doped metal-organic framework nanocore with a coupling product of hyaluronic acid and 3-aminophenylboronic acid.
[0011] Preferably, the preparation of the phenylboronic acid-functionalized hyaluronic acid layer includes the following steps: mixing hyaluronic acid solution, N-hydroxysuccinimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 3-aminophenylboronic acid in a liquid system, continuously stirring, reacting in the dark, and after the reaction is completed, dialysis and drying to obtain phenylboronic acid-functionalized hyaluronic acid material; preparing the phenylboronic acid-functionalized hyaluronic acid material into an aqueous solution, adding the in-situ EGCG-loaded copper-doped metal-organic framework nanonucleus, stirring in the dark, so that the phenylboronic acid-functionalized hyaluronic acid material is adsorbed and coated on the surface of the in-situ EGCG-loaded copper-doped metal-organic framework nanonucleus, forming a phenylboronic acid-functionalized hyaluronic acid layer; The pH of the hyaluronic acid solution is controlled to be 5.5-6.5.
[0012] Preferably, the mass ratio of the phenylboronic acid-functionalized hyaluronic acid material to the copper-doped metal-organic framework nanonucleus in situ loaded with EGCG is 0.8-1.2:1.
[0013] Preferably, the preparation of the M2 macrophage membrane biomimetic layer includes the following steps: preparing a mixed suspension of an in-situ EGCG-loaded copper-doped metal-organic framework nanonucleus coated with a phenylboronic acid-functionalized hyaluronic acid layer and an M2 macrophage membrane, and then performing membrane co-extrusion.
[0014] Preferably, the membrane co-extrusion uses a membrane with a pore size of 300-500 nm.
[0015] Preferably, the M2 macrophage membrane is taken from macrophages that have been induced by interleukin-4 to polarize to the M2 phenotype.
[0016] By adopting the above technical solution, the pH and ROS dual-responsive biomimetic EGCG nanomaterials of the present invention exhibit the following dual-responsiveness: under acidic conditions or ROS stimulation conditions, the release of EGCG from the pH and ROS dual-responsive biomimetic EGCG nanomaterials increases, and the release of EGCG further increases when acidic conditions and ROS stimulation work together. Specifically, the pH response is mainly provided by the acidic response of the copper-doped metal-organic framework nanocore, and the ROS response is mainly provided by the phenylboronic acid-functionalized hyaluronic acid layer.
[0017] Secondly, the preparation method of pH and ROS dual-responsive biomimetic EGCG nanomaterials provided by the present invention adopts the following technical solution: A method for preparing pH and ROS dual-responsive biomimetic EGCG nanomaterials includes the following steps: In situ-loaded EGCG copper-doped metal-organic framework nanonuclei and phenylboronic acid-functionalized hyaluronic acid material were prepared, and M2 macrophage membranes were extracted. The in situ-loaded EGCG copper-doped metal-organic framework nanonuclei were added to an aqueous solution of phenylboronic acid-functionalized hyaluronic acid material and stirred in the dark to obtain in situ-loaded EGCG copper-doped metal-organic framework nanonuclei coated with a phenylboronic acid-functionalized hyaluronic acid layer. The nanonuclei were then mixed with M2 macrophage membranes to form a suspension, and the membranes were co-extruded to obtain the pH and ROS dual-responsive biomimetic EGCG nanomaterials.
[0018] Preferably, the membrane co-extrusion uses a membrane with a pore size of 300-500 nm.
[0019] Thirdly, the present invention provides the application of pH and ROS dual-responsive biomimetic EGCG nanomaterials in the preparation of drugs for treating sepsis.
[0020] Fourthly, the present invention provides the application of a pH and ROS dual-responsive biomimetic EGCG nanomaterial in the preparation of a drug for reducing sepsis-related blood bacterial load.
[0021] Fifthly, the present invention provides the application of a pH and ROS dual-responsive biomimetic EGCG nanomaterial in the preparation of a drug for alleviating sepsis-related oxidative stress.
[0022] In a sixth aspect, the present invention provides the use of pH and ROS dual-responsive biomimetic EGCG nanomaterials in the preparation of medicaments for treating sepsis-related lung injury and / or sepsis-related liver injury and / or sepsis-related kidney injury.
[0023] In summary, the present invention has at least one of the following beneficial technical effects: This invention introduces EGCG in situ during the formation of a copper-doped metal-organic framework (MOF), and sequentially constructs a phenylboronic acid-functionalized hyaluronic acid layer and an M2-type macrophage membrane biomimetic layer, forming a pH and ROS dual-responsive biomimetic EGCG nanomaterial with multilayer functional synergy. The pH response is mainly provided by the acidic response of the copper-doped MOF nanocore, while the ROS response is mainly provided by the phenylboronic acid-functionalized hyaluronic acid layer. The M2-type macrophage membrane forms the biomimetic outer layer, which helps to endow the nanomaterial with biomimetic interface characteristics of the cell membrane and provides a structural basis for enhancing its interaction with the inflammatory microenvironment, improving the enrichment and retention of inflammatory sites, and reducing non-specific clearance in vivo. By loading EGCG onto the nanoframework and performing stepwise surface coating on the resulting nanoparticles, it is beneficial to reduce EGCG degradation during delivery, improve the stability and delivery efficiency of EGCG during delivery, and provide favorable conditions for effective EGCG delivery. Under acidic or ROS-stimulated conditions, EGCG release from the nanomaterials increased, and the release increased further when both conditions were combined, demonstrating EGCG release behavior responsive to both acidic conditions and ROS stimulation. This combined effect helps reduce serum IL-6 levels and blood bacterial load in CLP sepsis animal models, improves model survival, and alleviates pathological damage and oxidative stress in sepsis-related lung, liver, and kidney tissues. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the preparation process of the pH and ROS dual-responsive biomimetic EGCG nanomaterials in Example 1; Figure 2 These are the 1H NMR spectra of HA and HA-PBA in Example 1; Figure 3 The X-ray diffraction patterns are those of CZ obtained in Comparative Example 1, CZE in Example 1, and HP@CZE in Example 1. Figure 4 The results are the co-staining results of CD68 / CD206 immunofluorescence on RAW264.7 cells without IL-4 treatment and M2 type RAW264.7 cells induced by IL-4 in Example 1. Figure 5 These are transmission electron microscope (TEM) images of CZE, HP@CZE, and MM@HP@CZE in Example 1, and CZ in Comparative Example 1. Figure 6 This is a comparison diagram of the DLS hydration particle size distribution of CZE, HP@CZE and MM@HP@CZE in Example 1 and CZ in Comparative Example 1; Figure 7This is a comparison diagram of the zeta potentials of free EGCG, CZE, HP@CZE, MM, and MM@HP@CZE in Example 1 and CZ in Comparative Example 1; Figure 8 These are the HAADF-STEM and EDS elemental distribution analysis results of MM@HP@CZE in Example 1; Figure 9 This is a comparison chart of EGCG drug loading in CZE, HP@CZE and MM@HP@CZE in Example 1; Figure 10 This is a comparison graph of the cumulative EGCG release rate of MM@HP@CZE in different release media over time in Example 1; Figure 11 This is a comparison chart of the antibacterial rates of CZE, HP@CZE, and MM@HP@CZE in Example 1 and CZ prepared in Comparative Example 1; Figure 12 These are flow cytometry peaks of total reactive oxygen species-related fluorescence signals after CZE, HP@CZE, and MM@HP@CZE in Example 1 and CZ-treated inflammatory cell model in Comparative Example 1. Figure 13 This is a comparison of the average fluorescence intensity of total reactive oxygen species after CZE, HP@CZE, and MM@HP@CZE in Example 1 and CZ treatment of the inflammatory cell model in Comparative Example 1. Figure 14 This is a comparison of IL-6 levels in the supernatant of CZE, HP@CZE, and MM@HP@CZE in Example 1 and CZ-treated inflammatory cell model in Comparative Example 1. Figure 15 This is a comparison of the survival curves of mice in each group at 7 days when CZE, HP@CZE and MM@HP@CZE in Example 1 and CZ intervention in the mouse sepsis model in Comparative Example 1 were used. Figure 16 This is a comparison of serum IL-6 levels in mice of different groups when CZE, HP@CZE, and MM@HP@CZE were used in Example 1 and CZ was used in Comparative Example 1 to intervene in the mouse sepsis model. Figure 17 This is a comparison of the blood bacterial load of mice in each group when CZE, HP@CZE and MM@HP@CZE in Example 1 and CZ intervention in the mouse sepsis model in Comparative Example 1 are used. Figure 18 The results of H&E staining of lung, liver and kidney tissues of mice in each group when CZE, HP@CZE and MM@HP@CZE in Example 1 and CZ intervention in the mouse sepsis model in Comparative Example 1 are shown. Figure 19The results of ROS fluorescence staining and average fluorescence intensity analysis of lung, liver and kidney tissues of mice in each group when CZE, HP@CZE and MM@HP@CZE in Example 1 and CZ intervention in the mouse sepsis model in Comparative Example 1 are shown. Figure 20 This is a comparison chart of the hemolysis rates of CZE, HP@CZE and MM@HP@CZE in Example 1 and CZ prepared in Comparative Example 1 during the red blood cell hemolysis experiment; Figure 21 This is a comparison of cell viability after human umbilical vein endothelial cells treated with different concentrations of MM@HP@CZE prepared in Example 1. Detailed Implementation
[0025] The present invention will be further described in detail below with reference to the embodiments. The following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified, specific conditions in the following embodiments were performed under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the methods used are conventional methods known in the art, and the consumables and reagents used are commercially available. Unless otherwise stated, the technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be applied to the present invention.
[0026] The raw materials used in the examples and comparative examples are all commercially available.
[0027] Example 1 Example 1 of this invention provides a pH and ROS dual-responsive biomimetic EGCG nanomaterial, the preparation method of which is as follows: Preparation of copper-doped metal-organic framework nanonuclei in situ loaded with EGCG: 2.14 g of Zn(NO3)2·6H2O and 0.3479 g of Cu(NO3)2·3H2O were dissolved in a DMF / methanol mixed solvent (DMF to methanol volume ratio 4:1) to prepare a metal salt solution containing zinc and copper ions. 2.32 g of 2-methylimidazole and 0.20 g of EGCG were co-dissolved in an equal volume of DMF / methanol mixed solvent (DMF to methanol volume ratio 4:1) to prepare a ligand solution containing 2-methylimidazole and EGCG. Under continuous stirring and in the dark, the ligand solution containing 2-methylimidazole and EGCG was slowly added dropwise to the metal salt solution containing zinc and copper ions, and the reaction was carried out at room temperature for 24 h. During the formation of the copper-doped metal-organic framework material, EGCG was loaded into the nanoparticles through in-situ embedding and interaction with the nanoframework. The reaction product was centrifuged at 10,000 rpm for 10 min, washed three times with anhydrous ethanol, dried at 37 °C in the dark, and ground to obtain copper-doped metal-organic framework nanonuclei loaded with EGCG in situ, labeled as CZE.
[0028] Preparation of in-situ copper-doped metal-organic framework nanonuclei loaded with EGCG and coated with a phenylboronic acid-functionalized hyaluronic acid layer: 1.0 g of hyaluronic acid (HA) with a molecular weight of 100-200 kDa was added to 100 mL of deionized water and stirred until completely dissolved. The pH was adjusted to approximately 6.0 with dilute hydrochloric acid to obtain a hyaluronic acid solution. 0.57 g of N-hydroxysuccinimide (NHS), 0.77 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl), and 0.67 g of 3-aminophenylboronic acid were added sequentially to the hyaluronic acid solution. The mixture was stirred at room temperature in the dark for 48 h to allow the carboxyl groups of hyaluronic acid to undergo amidation coupling with the amino groups of 3-aminophenylboronic acid. The reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed with deionized water for 72 hours. h, followed by freeze-drying, yielded phenylboronic acid-functionalized hyaluronic acid material, labeled HA-PBA, abbreviated as HP. 50 mL of HA-PBA was prepared as a 1 mg / mL aqueous solution, and CZE was added at a 1:1 mass ratio of HA-PBA to CZE. The mixture was magnetically stirred for 3 h at room temperature and in the dark to allow HA-PBA to adsorb and coat the CZE surface, forming a phenylboronic acid-functionalized hyaluronic acid layer. After the reaction, the nanoparticles were collected by centrifugation, washed with deionized water, and freeze-dried to obtain in-situ EGCG-loaded copper-doped metal-organic framework nanonuclei coated with a phenylboronic acid-functionalized hyaluronic acid layer, labeled HP@CZE.
[0029] Preparation of pH and ROS dual-responsive biomimetic EGCG nanomaterials: Logarithmically growing RAW264.7 cells were induced for 48 h in complete DMEM medium containing 20 ng / mL mouse recombinant IL-4 to polarize them towards the M2 phenotype. The IL-4-induced M2-type RAW264.7 cells were collected, washed with pre-chilled PBS, and the cell pellet was resuspended in pre-chilled membrane protein extraction reagent containing 1 mM PMSF and incubated on ice for 15 min. Cells were lysed using three cycles of liquid nitrogen freeze-thaw, and centrifuged at 4 ℃, 700 g for 10 min to remove nuclei, incompletely lysed cells, and large fragments. The supernatant was collected and centrifuged at 4 ℃, 14,000 g for 30 min to precipitate cell membrane components. M2 macrophage membranes, labeled MM, were obtained by gently resuspending the membrane precipitate in pre-cooled PBS. HP@CZE and M2 macrophage membranes were separately prepared into suspensions and mixed. The mixture was then gently pipetted to ensure uniform dispersion, resulting in a mixed suspension. This mixture was repeatedly extruded 16 times through a 400 nm pore size polycarbonate membrane to promote the fusion of the M2 macrophage membrane and HP@CZE, forming an encapsulation structure. After extrusion, the mixture was centrifuged at 4 °C and 10,000 rpm for 10 min. The precipitate was collected, washed with PBS, and finally resuspended in PBS to obtain pH and ROS-responsive biomimetic EGCG nanomaterials, labeled MM@HP@CZE.
[0030] The schematic diagram of the preparation process of the pH and ROS dual-responsive biomimetic EGCG nanomaterials in this embodiment is shown below. Figure 1 As shown.
[0031] Comparative Example 1 Comparative Example 1 provides a copper-doped metal-organic framework material as a control. The preparation steps are as follows: 2.14 g of Zn(NO3)2·6H2O and 0.3479 g of Cu(NO3)2·3H2O were dissolved in a DMF / methanol mixed solvent (DMF to methanol volume ratio of 4:1) to prepare a metal salt solution containing zinc and copper ions; 2.32 g of 2-methylimidazole was dissolved in an equal volume of DMF / methanol mixed solvent (DMF to methanol volume ratio of 4:1) to prepare a ligand solution containing 2-methylimidazole. Under continuous stirring, the ligand solution containing 2-methylimidazole was slowly added dropwise to the metal salt solution containing zinc and copper ions, and the reaction was carried out at room temperature for 24 h. After the reaction was completed, the mixture was centrifuged at 10,000 rpm for 10 min, the precipitate was collected, washed three times with anhydrous ethanol, dried at 37 ℃, and ground to obtain the copper-doped metal-organic framework material, labeled CZ.
[0032] Testing and Inspection (1) The proton nuclear magnetic resonance spectra of HA and HA-PBA in Example 1 ( 1 The H NMR results are as follows Figure 2As shown; the X-ray diffraction (XRD) patterns of CZ obtained in Comparative Example 1, CZE in Example 1, and HP@CZE in Example 1 are as follows. Figure 3 As shown.
[0033] Reference Figure 2 The results showed that, compared with HA, HA-PBA exhibited a new proton signal in the 7-8 ppm aromatic hydrogen region, while retaining the N-acetylmethyl proton signal of HA at approximately 2.0 ppm, indicating that the PBA group had been successfully introduced into the HA molecular chain, successfully forming HA-PBA. (Reference) Figure 3 The results showed that CZ exhibited the main characteristic diffraction peaks of ZIF-8 (zeolite imidazole ester framework material-8) metal-organic framework. Compared with CZ, CZE and HP@CZE still retained similar main diffraction peaks, and the peak positions did not shift significantly, indicating that the basic crystal structure of copper-doped ZIF-8 nanoframework was still preserved after in-situ loading of EGCG and coating with HA-PBA.
[0034] (2) Phenotypic identification was performed on RAW264.7 cells (labeled M0) that were not treated with IL-4 and M2 type RAW264.7 cells (labeled M2) induced by IL-4 in Example 1 using CD68 / CD206 immunofluorescence co-staining. The results are as follows: Figure 4 As shown, CD68 is a macrophage-related marker, and CD206 is an M2-related marker.
[0035] Reference Figure 4 The results showed that CD68 positive fluorescence signals could be observed in both M0 and M2 RAW264.7 cells. After IL-4 induction, the CD206 fluorescence signal in the M2 group was enhanced compared with that in the M0 group, indicating that IL-4 induction can induce RAW264.7 cells to exhibit M2 phenotype characteristics. This indicates that RAW264.7 cells are polarized towards the M2 phenotype under IL-4 induction, and M2 type RAW264.7 cells were successfully obtained, providing a cell source for the subsequent extraction of M2 type macrophage membranes.
[0036] (3) Transmission electron micrographs (TEM) of CZE, HP@CZE, and MM@HP@CZE in Example 1 and CZ in Comparative Example 1 (JEM-2100F transmission electron microscope, JEOL Ltd. (Tokyo, Japan)) are shown below. Figure 5 As shown; the particle size distribution was determined using a Zetasizer Nano ZS particle size and Zeta potential analyzer (Malvern Panalytical Ltd. (Malvern, UK)) and dynamic light scattering (DLS) method. The DLS hydrated particle size distribution results are shown below. Figure 6As shown, the zeta potentials of free EGCG, CZE, HP@CZE, MM, and MM@HP@CZE in Example 1 and CZ in Comparative Example 1 were measured using electrophoretic light scattering. The results are as follows. Figure 7 As shown.
[0037] Reference Figure 5 and Figure 6 CZ, CZE, HP@CZE, and MM@HP@CZE all exhibited nanoscale hydration particle size distributions, primarily concentrated in the range of approximately 100-400 nm. Among them, the particle size distribution of EGCG-loaded CZE was closer to that of CZ; after HA-PBA coating, the hydration particle size distribution of HP@CZE shifted towards larger particle sizes; further coating with M2 macrophage membranes resulted in an even greater shift in the hydration particle size distribution of MM@HP@CZE towards larger particle sizes. Figure 6 The particle size distribution curves show that the main distribution peaks of each material are generally located in the range of approximately 170-230 nm, and tend to shift towards larger particle sizes with each level of coating. Combined with... Figure 5 It can be observed that the morphology of the outer edge of the particles changes after HA-PBA coating, and a membrane-like structure appears on the periphery of the particles after further coating with the M2 macrophage membrane. (Refer to...) Figure 7 The zeta potential of the materials changed accordingly at different construction stages. The zeta potential of HP@CZE shifted towards a more neutral direction compared to CZE. After being coated with the M2 macrophage membrane, MM@HP@CZE became negatively charged, and its zeta potential fell between that of HP@CZE and the M2 macrophage membrane. These results, along with the changes in particle morphology, hydrated particle size distribution, and surface potential, collectively support the stepwise construction of MM@HP@CZE nanomaterials.
[0038] (4) The HAADF-STEM and EDS elemental distribution of MM@HP@CZE in Example 1 were analyzed using a Talos F200X scanning transmission electron microscope (Thermo Fisher Scientific (Hillsboro, OR, USA)). The results are as follows: Figure 8 As shown.
[0039] Reference Figure 8 C, N, O, Zn, and Cu elemental signals were detected within the MM@HP@CZE particle region. Zn and Cu signals were present in both nanoparticle regions, indicating that MM@HP@CZE retains copper and zinc elements. Combined with the aforementioned XRD, TEM, DLS, and Zeta potential characterization results, this further supports the stepwise construction of MM@HP@CZE nanomaterials.
[0040] (5) The EGCG loading of CZE, HP@CZE, and MM@HP@CZE in Example 1 was determined by the ferrous tartrate colorimetric method. CZE, HP@CZE, and MM@HP@CZE were dispersed in PBS solution at pH 5.4 containing 10 mM H2O2 to a nanomaterial concentration of 1 mg / mL. The solution was continuously shaken at 37 ℃ for 72 h to promote the full release of the loaded EGCG. The supernatant was collected by centrifugation, and the absorbance was measured at 540 nm. The loading was calculated based on the EGCG standard curve. The results are as follows: Figure 9 As shown; MM@HP@CZE from Example 1 was placed in release media at pH 7.4, pH 7.4 containing 10 mM H2O2, pH 5.4, and pH 5.4 containing 10 mM H2O2, respectively, with a concentration controlled at 1 mg / mL. An in vitro release experiment was conducted at 37 ℃ and 100 rpm for 48 h, and samples were taken at set time points to determine the cumulative release rate of EGCG. The results are as follows. Figure 10 As shown.
[0041] Reference Figure 9 The EGCG loading capacities of CZE, HP@CZE, and MM@HP@CZE were 10.730%, 9.545%, and 8.471%, respectively, indicating that MM@HP@CZE could still effectively load EGCG after being progressively coated with HA-PBA and the M2 macrophage membrane. (Reference) Figure 10 MM@HP@CZE exhibited relatively slow EGCG release at pH 7.4; however, EGCG release increased under both H2O2 stimulation and acidic conditions at pH 5.4; under the combined effects of pH 5.4 and H2O2, EGCG release further increased, reaching the highest level among the four groups. These results indicate that MM@HP@CZE possesses a dual-responsive EGCG release characteristic to both pH and ROS.
[0042] (6) Using *Escherichia coli* and *Staphylococcus aureus* as test bacteria, the in vitro antibacterial activity of CZE, HP@CZE, and MM@HP@CZE in Example 1 and CZ prepared in Comparative Example 1 was compared using the plate colony counting method. *Escherichia coli* and *Staphylococcus aureus* in logarithmic growth phase were co-incubated with CZ, CZE, HP@CZE, and MM@HP@CZE, respectively, with a final concentration of 1000 μg / mL. Bacterial suspensions without the above nanomaterials were used as the control group. After incubation, the bacterial suspensions of each group were serially diluted, and the appropriate dilution was spread onto the surface of a solid culture medium. After incubation at 37 ℃, colony forming units (CFU) were counted. The antibacterial rate of each group was calculated according to the following formula: Antibacterial rate (%) = (1 The formula is calculated as (CFU_sample / CFU_CON) × 100%, where CFU_sample is the number of colony-forming units (CFU) in the nanomaterial treatment group and CFU_CON is the number of CFU in the control group. The results are as follows: Figure 11 As shown.
[0043] Reference Figure 11 The results showed that CZ, CZE, HP@CZE, and MM@HP@CZE all exhibited varying degrees of in vitro antibacterial activity against *Escherichia coli* and *Staphylococcus aureus*, with CZE showing the highest antibacterial rate. After stepwise coating with HA-PBA and M2 macrophage membranes, the antibacterial rates of HP@CZE and MM@HP@CZE decreased compared to CZE, but they still maintained significant in vitro antibacterial activity. These results indicate that EGCG loading can enhance the in vitro antibacterial activity of copper-doped ZIF-8 nanomaterials. After stepwise coating with HA-PBA and M2 macrophage membranes, the resulting nanomaterials still retained their in vitro antibacterial ability against *Escherichia coli* and *Staphylococcus aureus*. The change in antibacterial rate after stepwise coating may be related to the outer structure's barrier to direct contact between the nanocore and bacteria, and its influence on the EGCG release process. Figure 10 The results show that MM@HP@CZE releases EGCG relatively slowly at pH 7.4, while acidic conditions or H2O2 stimulation can promote EGCG release. When both conditions work together, EGCG release increases further. This indicates that MM@HP@CZE maintains its in vitro antibacterial activity while also exhibiting pH and ROS-responsive EGCG release characteristics. This is beneficial for maintaining relatively slow EGCG release under non-stimulatory conditions, while accelerating EGCG release under specific microenvironmental conditions with acidic conditions and high ROS levels.
[0044] (7) Establishing an LPS-induced RAW264.7 cell inflammation model: RAW264.7 cells were seeded in cell culture plates and cultured at 37 ℃ and 5% CO2. After the cells adhered and reached a suitable density, LPS with a final concentration of 100 ng / mL was added for 12 h to establish an inflammatory cell model. After LPS stimulation, CZE, HP@CZE, and MM@HP@CZE from Example 1 and CZ from Comparative Example 1 were added to the above-mentioned inflammatory model cells for intervention. The final concentration of each nanomaterial was 20 μg / mL. Cells that did not receive LPS and the above-mentioned nanomaterial treatment were used as the control group (CON group), cells that only received LPS treatment were used as the model group (LPS group), and cells that were given CZ, CZE, HP@CZE and MM@HP@CZE on the basis of LPS treatment were used as the corresponding nanomaterial treatment groups. After treatment, RAW264.7 cells in each group were fluorescently labeled using the ROS-ID Total ROS Detection Kit (Enzo Life Sciences, ENZ-51011), and the total reactive oxygen species-related fluorescence signals were detected by flow cytometry. The flow cytometry peak diagram of the total reactive oxygen species-related fluorescence signals is shown below. Figure 12 As shown, the comparison results of mean fluorescence intensity (MFI) are as follows: Figure 13 As shown; simultaneously, cell culture supernatants from each group were collected, and IL-6 levels were detected using a mouse IL-6 ELISA kit (Elabscience, E-EL-M0044). The results are shown below. Figure 14 As shown.
[0045] Reference Figure 12 and Figure 13 Compared with the CON group, the total reactive oxygen species (ROS)-related fluorescence signal and MFI of RAW264.7 cells were significantly increased after LPS stimulation. Compared with the LPS group, the total ROS-related fluorescence signal was decreased to varying degrees after CZE, HP@CZE, and MM@HP@CZE treatment, with the most significant overall decrease observed in the MM@HP@CZE group. (Reference) Figure 14 LPS stimulation increased IL-6 levels in cell culture supernatant. Treatment with CZE, HP@CZE, and MM@HP@CZE resulted in varying degrees of decrease in IL-6 levels, with the MM@HP@CZE group showing the lowest IL-6 level. These results indicate that MM@HP@CZE can reduce LPS-induced intracellular total reactive oxygen species levels in RAW264.7 cells and inhibit the secretion of the pro-inflammatory cytokine IL-6, suggesting its role in regulating oxidative stress and inflammatory responses in inflammatory macrophages.
[0046] (8) A mouse sepsis model was established using the cecal ligation and perforation method. The specific steps were as follows: Mice were anesthetized with isoflurane and fixed in a supine position. The abdomen was prepared and disinfected. Under aseptic conditions, the abdominal cavity was opened and the cecum was exposed. The cecum was ligated at about 1 / 2 of its distal end. The cecum was punctured 1–2 times with a 21 G sterile injection needle, and a small amount of intestinal contents was gently squeezed out from the perforation. The cecum was then returned to the abdominal cavity and sutured layer by layer. Mice in the CON group received sham surgery, that is, only the abdomen was opened and the cecum was exposed, without cecal ligation and perforation. Mice were randomly divided into CON group, CLP group, CZ group, CZE group, HP@CZE group and MM@HP@CZE group. One hour after CLP modeling, CZ group, CZE group, HP@CZE group and MM@HP@CZE group were administered CZ prepared in Comparative Example 1 and CZE, HP@CZE and MM@HP@CZE prepared in Example 1 via tail vein injection, respectively. The dosage was 25 mg / kg. CON group and CLP group were given an equal volume of PBS.
[0047] The survival status of mice in each group was continuously observed for 7 days and survival curves were plotted. The results are as follows: Figure 15 As shown in the figure. Blood was collected from mice in each group 24 h after the corresponding intervention. Serum was separated by centrifugation, and serum IL-6 levels were detected using a mouse IL-6 ELISA kit (Elabscience, E-EL-M0044). The results are shown in the figure. Figure 16 As shown. 24 h after the corresponding intervention, anticoagulated blood was collected from mice in each group under aseptic conditions and serially diluted. The blood dilutions at appropriate dilution ratios were evenly spread on the surface of solid agar medium and incubated at 37 ℃ for 24 h. Colony forming units (CFU) were then counted. Blood bacterial load was expressed as CFU / mL and analyzed using logarithmic methods. 10 After conversion, statistical analysis was performed, and the results are as follows: Figure 17 As shown; lung, liver, and kidney tissues of mice in each group were collected 24 h after the corresponding intervention and H&E staining was performed to observe histopathological changes. The results are as follows. Figure 18 As shown; other corresponding tissues were taken for ROS fluorescence staining, and the average fluorescence intensity was used to perform semi-quantitative analysis of ROS-related fluorescence signals. The results are as follows. Figure 19 As shown.
[0048] Reference Figure 15 Compared with the CLP group, the survival rate of mice treated with MM@HP@CZE was significantly improved after 7 days. (Reference) Figure 16 Compared with the CON group, the serum IL-6 level in the CLP group mice was significantly increased; after treatment with CZE, HP@CZE, and MM@HP@CZE, serum IL-6 levels decreased to varying degrees, with the MM@HP@CZE group showing the most significant overall decrease. (Reference) Figure 17Compared with the CLP group, the blood bacterial load of mice in each nanomaterial treatment group was reduced to varying degrees, with the MM@HP@CZE group showing the most significant overall reduction. These results indicate that MM@HP@CZE can improve the survival status of CLP-treated septic mice, reduce serum IL-6 levels and blood bacterial load, thereby alleviating sepsis-related systemic inflammatory response and bacterial load. (Reference) Figure 18 and Figure 19 Compared with the CLP group, the pathological damage to the lung, liver, and kidney tissues of mice in the MM@HP@CZE group was improved to varying degrees, and the ROS-related fluorescence signals in the corresponding tissues were reduced. These results indicate that MM@HP@CZE can alleviate oxidative stress and pathological damage to sepsis-related lung, liver, and kidney tissues, demonstrating its protective effect against sepsis-related multi-organ damage.
[0049] (9) The hemolysis test was used to evaluate the blood compatibility of CZE, HP@CZE, and MM@HP@CZE in Example 1 and CZ prepared in Comparative Example 1. Fresh anticoagulated blood was collected from mice, and red blood cells were separated by centrifugation. After washing three times with physiological saline, the red blood cell suspension was prepared by resuspending. The red blood cell suspension was incubated with CZ, CZE, HP@CZE, and MM@HP@CZE, respectively. The final concentration of each nanomaterial was 0.1 mg / mL. The physiological saline treatment group was used as a negative control, and the deionized water treatment group was used as a positive control. After incubation at 37 ℃ in the dark for 3 h, the supernatant was collected by centrifugation. The absorbance was measured at 540 nm and the hemolysis rate was calculated. The results are as follows. Figure 20 As shown.
[0050] The cytocompatibility of MM@HP@CZE prepared in Example 1 with human umbilical vein endothelial cells (HUVECs) was evaluated using the CCK-8 assay. HUVECs were seeded in 96-well plates and cultured. After cell attachment, different concentrations of MM@HP@CZE were added for treatment, with the nanomaterial concentration ranging from 0.1 to 500 μg / mL. After 24 h of treatment, CCK-8 reagent was added for further incubation for 2 h. Absorbance was measured at 450 nm and cell viability was calculated. The results are as follows: Figure 21 As shown.
[0051] Reference Figure 20 The hemolysis rates of the CZ, CZE, HP@CZE, and MM@HP@CZE treatment groups were all at low levels, indicating that the above nanomaterials did not produce significant hemolytic effects on erythrocytes and have good in vitro blood compatibility. (Reference) Figure 21Within a concentration range of 0.1–200 μg / mL, the viability of HUVEC cells treated with MM@HP@CZE remained at a high level, indicating that MM@HP@CZE has good HUVEC cell compatibility within this concentration range. These results support the good in vitro biocompatibility of MM@HP@CZE in terms of blood compatibility and endothelial cell compatibility.
[0052] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A pH and ROS dual-responsive biomimetic EGCG nanomaterial, characterized in that: It includes, from the inside out, a copper-doped metal-organic framework nanonucleus loaded with EGCG in situ, a phenylboronic acid-functionalized hyaluronic acid layer, and an M2 macrophage membrane biomimetic layer.
2. The pH and ROS dual-responsive biomimetic EGCG nanomaterial according to claim 1, characterized in that: The preparation of the copper-doped metal-organic framework nanonucleus loaded with EGCG in situ includes the following steps: adding a ligand solution containing 2-methylimidazole and EGCG to a metal salt solution containing zinc ions and copper ions, stirring continuously, and reacting in the dark.
3. The pH and ROS dual-responsive biomimetic EGCG nanomaterial according to claim 2, characterized in that: The mass ratio of 2-methylimidazole to EGCG in the ligand solution containing 2-methylimidazole and EGCG is 10-15:
1.
4. The pH and ROS dual-responsive biomimetic EGCG nanomaterial according to claim 2, characterized in that: The molar ratio of zinc ions to copper ions in the metal salt solution containing zinc ions and copper ions is 4-6:
1.
5. The pH and ROS dual-responsive biomimetic EGCG nanomaterial according to claim 1, characterized in that: The preparation of the phenylboronic acid-functionalized hyaluronic acid layer includes the following steps: hyaluronic acid solution, N-hydroxysuccinimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 3-aminophenylboronic acid are mixed in a liquid system, continuously stirred, and reacted in the dark. After the reaction is completed, the mixture is dialyzed and dried to obtain the phenylboronic acid-functionalized hyaluronic acid material; the phenylboronic acid-functionalized hyaluronic acid material is prepared into an aqueous solution, and the copper-doped metal-organic framework nanonucleus loaded with EGCG in situ is added. The mixture is stirred in the dark, so that the phenylboronic acid-functionalized hyaluronic acid material is adsorbed and coated on the surface of the copper-doped metal-organic framework nanonucleus loaded with EGCG in situ, forming a phenylboronic acid-functionalized hyaluronic acid layer; The pH of the hyaluronic acid solution is controlled to be 5.5-6.
5.
6. The pH and ROS dual-responsive biomimetic EGCG nanomaterial according to claim 5, characterized in that: The mass ratio of the phenylboronic acid-functionalized hyaluronic acid material to the copper-doped metal-organic framework nanonucleus in situ loaded with EGCG is 0.8-1.2:
1.
7. The pH and ROS dual-responsive biomimetic EGCG nanomaterial according to claim 1, characterized in that: The preparation of the biomimetic layer of the M2 macrophage membrane includes the following steps: preparing a mixed suspension of an in-situ copper-doped metal-organic framework nanonucleus loaded with EGCG and an M2 macrophage membrane coated with a phenylboronic acid-functionalized hyaluronic acid layer and performing membrane co-extrusion.
8. The pH and ROS dual-responsive biomimetic EGCG nanomaterial according to claim 7, characterized in that: The M2 macrophage membrane was obtained from macrophages that were induced by interleukin-4 to polarize to the M2 phenotype.
9. A method for preparing pH and ROS dual-responsive biomimetic EGCG nanomaterials as described in any one of claims 1-8, characterized in that: Includes the following steps: In situ-loaded EGCG copper-doped metal-organic framework nanonuclei and phenylboronic acid-functionalized hyaluronic acid material were prepared, and M2 macrophage membranes were extracted. The in situ-loaded EGCG copper-doped metal-organic framework nanonuclei were added to an aqueous solution of phenylboronic acid-functionalized hyaluronic acid material and stirred in the dark to obtain in situ-loaded EGCG copper-doped metal-organic framework nanonuclei coated with a phenylboronic acid-functionalized hyaluronic acid layer. The nanonuclei were then mixed with M2 macrophage membranes to form a suspension, and the membranes were co-extruded to obtain the pH and ROS dual-responsive biomimetic EGCG nanomaterials.
10. The use of a pH and ROS dual-responsive biomimetic EGCG nanomaterial as described in any one of claims 1-8 in the preparation of a medicament for treating sepsis.